Cell phenotype and cytokine regulation of erythropoiesis in mouse fetal spleen - Tan, Keai Sinn (2015)
Erythropoiesis and its regulation have been extensively studied in the yolk sac, fetal liver and bone marrow, but not on the regulation of spleen erythropoiesis in the mouse embryo. Fetal spleen was reportedly a major hematopoietic site prior to initiation of bone marrow hematopoiesis. Morphologic analysis suggested erythropoietic activity in fetal spleen, but it remained unclear how erythropoiesis was regulated. To address this question, flow cytometric analysis was performed and the number of spleen erythroid cells was found to increase 18.6-fold from 16.5 days post-coitum (dpc) to 19.5 dpc. Flow cytometric analysis was carried out to further characterize fetal spleen cells. Among CD45-Ter119- non-hematopoietic cells at 16.5 dpc fetal spleen, 9.87±1.12% were DLK-1-expressing cells, 0.32±0.14% were microvessels, 31.09±17.75% were endothelial cells and 62.01±23.03% were unclassified cells. Whereas at 19.5 dpc fetal spleen, 2.00±0.38% were DLK-1-expressing cells, 0.96±0.36% were microvessels, 57.75±18.34% were endothelial cells and 38.82±17.88% were unclassified cells. Realtime PCR was carried out to investigate whether those fetal spleen cells express erythropoietic cytokines such as stem cell factor (Scf), insulin growth factor 1 (Igf1), interleukin-3 (Il-3) and erythropoietin (Epo) messenger RNAs (mRNAs). Of these erythropoietic cytokines, at 16.5 dpc whole spleen cells, both Scf and Igf1 mRNAs were highly expressed, while Epo and Il-3 mRNAs were not. Among erythropoietic cytokines, SCF and IGF-1 proteins were primarily expressed in hematopoietic, endothelial and mesenchymal-like fetal spleen cells. Further examination of the expression of SCF receptor (c-Kit) and the IGF-1 receptor (IGF-1R) on spleen erythroid cells performed by flow cytometric analysis shows that most of the c-Kit+ and IGF-1R+ cells were expressed on burst forming unit-erythroid (BFU-E) and colony forming unit-erythroid (CFU-E) equivalent cells. Cultures treated with SCF and/or IGF-1R inhibitors showed significantly decreased CD45c-KitCD71+/Ter119+ erythroid cells and down-regulated Gata1, Klf1 and β-major globin expression. Administration of these inhibitors to pregnant mice significantly decreased the number of CD45c-KitCD71+/Ter119+ cells and down-regulated β-major globin gene expression in embryos derived from these mice. We conclude that fetal spleen is a site where erythropoietic activity takes place and spleen endothelial and mesenchymal-like cells primarily accelerate erythropoietic activity through SCF and IGF-1 secretion.